Self-esteem in pregnant adolescents and its relationship with family functionality and social support - Vazquez Cruz, Carlos Alejandro; Cruz Cruz, Yamileth Yurithzi; Hernández Mariano, José Ángel; Mendoza Mojica, Sheila Adriana; Cano Estrada, Edith Araceli (Horizonte Sanitario, 2025)
Objetive: To identify the association between family functionality and social support with the level of self-esteem of pregnant adolescents in a rural community of the Mezquital Valley in the state of Hidalgo, Mexico.Materials and methods: Analytical and cross-sectional study with non-probability sampling by disposition. We worked with a sample of 150 pregnant adolescents belonging to the municipality of Tezontepec de Aldama, to whom the family APGAR instrument, the Rosemberg self-esteem scale and the social support scale were administered. The level of self-esteem was compared with family functionality and social support using Pearson's Chi2. To evaluate the association of variables, logistic regression models adjusted for confounding variables were used.Results: The study was dominated by adolescents who live with their partners, who are dedicated to the home and who already had a child. Significant differences (p < 0.05) were found between the level of self-esteem of adolescents who receive support regularly and those who do not receive support; as well as between adolescents without family dysfunction and those with family dysfunction. Finally, it was found that adolescents without regular social support are more likely to have low self-esteem (RM=4.8 CI=1.97-12.10) and similarly, those adolescents with some degree of family dysfunction are more likely to have low self-esteem (RM=3.74, CI=1.37-10.88).Conclusions: A dysfunctional family environment and lack of social support are directly associated with low self-esteem in pregnant adolescents. Therefore, it is necessary to implement support interventions to increase social and family ties, and thus improve the adolescent's overall confidence and mental health, to cope with pregnancy and motherhood in a healthy way. Keywords: Adolescent, pregnancy; mental health; social support; family.